Scaling procedures issues and applications - Netemeyer, Richard G., 1956-; Bearden, William O., 1945-; Sharma, Subhash (Thousand Oaks, Calif. ; London : SAGE, 2003)
'Scaling Procedures' examines the issues involved in developing and validating multi-item self-report scales of latent constructs. It supplies cutting-edge strategies for developing and refining measures.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Scaling (Social sciences)